Introduction to Social Systems Engineering - Wang, Huijiong (Springer Singapore, 2018)
This book integrates the basic theories (GST and Parson's AGIL framework), applying them to the components of social systems, state-run and business firms. China's development experience offers a valuable case study that can provide readers deeper insights into this comparatively young discipline, and into China. Though the discipline of systems engineering and its application to hardware engineering system are well established, social systems engineering is an emerging discipline still being explored. This book may be the first English-language publication on this promising subject.